Stakeholders: Strategic Actors in Brand Building (2018)
The stakeholders, also known as groups of interest, are increasingly important for brand building, especially because of the need to generate differentiated communication on the part of the company, which must demonstrate a solid identity that generates processes for the creation of a correct image and a strong corporate reputation. In this aspect, this article meets a priority need: to know the groups of interest for the creation of brand building strategies, even from current tools such as experiential marketing. For this, a theoretical review of recognized authors in the field of branding, corporate communication, and marketing was carried out through specialized databases: academic texts, research, and scientific articles were taken into account. After having these inputs, relevant topics for the study of the stakeholders and their relationship with the communication of the companies were developed. This allowed for a detailed analysis of the company's intangibles, which contributes to the generation of useful knowledge for the field of branding. The main conclusions revolve around the relevance that stakeholders have in the management of the identity of the brand, with a view to generating a correct image and corporate reputation. This issue is key in the communication of any company, because currently the proper management of intangibles is the key to business success, and a good link with different stakeholders.